1986
DOI: 10.1111/j.1532-5415.1986.tb05767.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' and Physicians' Attitudes Toward Tube‐Feeding Decisions in Long‐Term Care

Abstract: We studied attitudes of health professionals toward life-sustaining treatment. A patient management questionnaire sent to staff physicians and nurses in 183 Oregon nursing homes consisted of eight patient sketches which varied age, mental status, and enjoyment of life. Respondents were asked whether they would favor tube-feeding to correct malnutrition in each case. Nurses showed higher preferences for tube-feeding than did physicians (P = .05). For both professions, patient happiness was the strongest and mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2
2

Year Published

1990
1990
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 16 publications
3
31
2
2
Order By: Relevance
“…There appears to be general agreement amongst health care professionals that the de cision for PEG referral should be multidisci plinary and that carers' views should be sought. This is especially important in the long-term care setting where ethical decision making can be difficult [ 15], This survey suggests that the profesional's perception of an individual's quality of life plays an important role in decision making and that age itself is the least likely factor to influence referral for PEG feeding. This is in contrast to a previous study which investi gated the influence of patient's age on medical decision to attempt treatment in critically ill patients [24], This early study showed that physicians tended to treat older patients less aggressively than middle-aged patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There appears to be general agreement amongst health care professionals that the de cision for PEG referral should be multidisci plinary and that carers' views should be sought. This is especially important in the long-term care setting where ethical decision making can be difficult [ 15], This survey suggests that the profesional's perception of an individual's quality of life plays an important role in decision making and that age itself is the least likely factor to influence referral for PEG feeding. This is in contrast to a previous study which investi gated the influence of patient's age on medical decision to attempt treatment in critically ill patients [24], This early study showed that physicians tended to treat older patients less aggressively than middle-aged patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to a previous study which investi gated the influence of patient's age on medical decision to attempt treatment in critically ill patients [24], This early study showed that physicians tended to treat older patients less aggressively than middle-aged patients. A fur ther study [15] has reported that younger pa tients were given higher preference for tube feeding than were older patients. These au thors concluded that the reasons for this may include the reduced ability of elderly subjects to recover from serious illnesses, poor toler ance of invasive therapy, and perceived poor quality of life due to multiple physical and social problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 By contrast, physicians experienced in the care of the elderly are less willing to favour any form of tube feeding in severely demented patients. 24 In Canadian studies, 30% of carers who had consented to PEG insertion subsequently expressed uncertainty about whether the right decision had been made. 25,26 Factors considered to have influenced the giving of consent were emotional involvement with the patient, religious or moral convictions, lack of understanding about prognosis and a fear of death by starvation for the patient if no PEG were inserted.…”
Section: Ethical Dilemmas In Peg Feeding Demented Patientsmentioning
confidence: 99%
“…A survey of 141 American physicians found that cognition and life expectancy were relatively minor influences on the physician's decisions regarding tube feeding of nursing home residents (Von Preyss-Friedman et al 1992). Conversely, Watts et al (1986) found that the mental status of the patient significantly influenced physicians' (n 124) preferences for tube feeding patients. Younger patients tended to be given higher preferences for tube feeding, and the happiness of the patient was the strongest and most significant influence on the physician's preference.…”
Section: Opinions Of Health Professionalsmentioning
confidence: 99%